2017
DOI: 10.1289/ehp1849
|View full text |Cite
|
Sign up to set email alerts
|

Ambient Ozone Pollution and Daily Mortality: A Nationwide Study in 272 Chinese Cities

Abstract: Background:Few large multicity studies have been conducted in developing countries to address the acute health effects of atmospheric ozone pollution.Objective:We explored the associations between ozone and daily cause-specific mortality in China.Methods:We performed a nationwide time-series analysis in 272 representative Chinese cities between 2013 and 2015. We used distributed lag models and over-dispersed generalized linear models to estimate the cumulative effects of ozone (lagged over 0–3 d) on mortality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
154
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 283 publications
(194 citation statements)
references
References 38 publications
12
154
0
Order By: Relevance
“…We further explored potential effect modification of COPD risk by sex, age (18-64 years and ≥65 years), and season (warm: April to September; cool: October to March) using concurrent day PM 2.5 concentration. A penalized spline function of calendar time on warm or cool season was used to accommodate the long-term trend in hospital visits for COPD [30,31]. The statistical significance of subgroup differences were tested using the Z-test [32].…”
Section: Discussionmentioning
confidence: 99%
“…We further explored potential effect modification of COPD risk by sex, age (18-64 years and ≥65 years), and season (warm: April to September; cool: October to March) using concurrent day PM 2.5 concentration. A penalized spline function of calendar time on warm or cool season was used to accommodate the long-term trend in hospital visits for COPD [30,31]. The statistical significance of subgroup differences were tested using the Z-test [32].…”
Section: Discussionmentioning
confidence: 99%
“…It is an oxidant air pollutant generated by photochemical reactions involving nitrogen oxides and volatile organic compounds. Short-term effects of ozone on mortality and morbidity have been reported in the epidemiological literature, among others from large multi-center studies conducted in Europe [13,14], the United States [15], and China [16]. The effects of long-term exposure to ozone on human health has however not been fully established [17].…”
Section: Introductionmentioning
confidence: 99%
“…Long-term exposure to greater concentrations of O3 (the highest quintile f of exposure concentrations, 82-112 µg m -3 ) was associated with increased incidence of hypertension (HR = 1.09, 95% CI; 1.00-1.18) but the opposite was reported for NO2 (48-73 µg m -3 ) where higher NO2 concentrations were related to lower incidence (HR = 0.92, 95% CI; 0.86-0.98). In a 272-city study in China for data from 2013-2015, 89 a positive association between 10 µg m -3 increments in concentration of O3 and higher daily mortality was reported from cardiovascular diseases (0.27%, 95%, PI = 0.10-0.44%), including hypertension (0.60%. 95% PI = 0.08-1.11%), coronary diseases (0.24%, 95%, PI = 0.02-0.46%), and stroke (0.29%, 95%PI = 0.07-0.50%).…”
Section: Overview Of Recent Human Health Studiesmentioning
confidence: 98%
“…88 A nationwide study in 272 Chinese cities between 2013 and 2015 showed that a 0.24% increase in daily mortality from all nonaccidental causes (95% Prediction Interval (PI c ) = 0.13%-0.35%) was associated with an increment in 8-h maximum concentration of O3 of 10 µg m -3 , approximately half that reported above. 89 However, no association between increased concentrations of O3 and daily mortality from respiratory diseases was reported.…”
Section: Overview Of Recent Human Health Studiesmentioning
confidence: 99%